An investigation of the interactions between methadone and elvitegravir/cobicistat in subjects receiving chronic methadone maintenance. - Bruce, R Douglas; Winkle, P; Custodio, Jm; Wei, X; Rhee, M S; Kearney, Bp; Ramanathan, S; Friedland, Gerald H (Antimicrobial agents and chemotherapy, 2013)
Aim: Interactions between HIV and opioid-dependence therapies are known to occur. We sought to determine if such interactions occurred between methadone and elvitegravir boosted with cobicistat.Methods: We performed a within-subject open labeled pharmacokinetic and pharmacodynamic study in eleven HIV-seronegative subjects stabilized on at least 2 weeks of methadone. Subjects underwent baseline and steady-state evaluation of the effect of elvitegravir 150 mg qD boosted with 150 mg qD of cobicistat (EVG/COBI) on methadone pharmacokinetic parameters. Safety and pharmacodynamics were monitored throughout the study.Results: Compared to baseline values, R-methadone mean AUCtau (5550 vs. 6210 hr*ng/mL) and mean Cmax (316 vs. 337 ng/mL) did not significantly increase in the presence of EVG/COBI. Compared to baseline values, S-methadone mean AUCtau (7040 vs. 7540 hr*ng/mL) and mean Cmax (446 vs. 452 ng/mL) did not significantly increase in the presence of EVG/COBI. The AUCtau, Cmax and Ctau of elvitegravir and cobicistat did not significantly differ from historical controls. Opioid withdrawal or overdose was not observed among subjects in this study.Conclusion: The addition of EVG/COBI to stabilized patients receiving methadone did not affect methadone pharmacodynamics. The two can be safely co-administered.